DEVELOPMENT PROCESS OF A FOOD AND NUTRITION EDUCATION PROGRAM FOR ADOLESCENT BRAZILIAN VOLLEYBALL PLAYERS (Fiep Bulletin - online, 2014)
Young athletes are vulnerable regarding the adoption of inadequate nutrition aiming to achieve weight/body composition and performance goals. The aim of this study is to describe the process of development of a Food and Nutrition Program for female adolescent Brazilian volleyball athletes. The team comprises 14 girls (17.3±1.0 years old; training 16 hours/week). Quantitative and qualitative data were collected to bring subsidies for the development of a customized program. Athletes answered questions on nutritional knowledge and beliefs, body perception and intention of changing eating behavior. Knowledge score was of 57% correct answers. Athletes showed lack of knowledge on nutritional composition and food groups. As beliefs, protein was overvalued and hydration concepts misunderstood. Body distortion was observed in 29% of the sample. Regarding the intention of behavior change, athletes were classified in the “action” (46%) stage. A discussion group was held to investigate athletes´ perception and feelings towards food and pressure for results, lack of time to prepare meals and doubts about what to eat to improve performance were the main issues. Based on these results and adopting a problematization methodology (Maguerez Arch) 6 meetings were planned in which ludic and participatory activities were chosen to stimulate participation. Topics comprise: balanced eating, health and performance, hydration strategies, body perception and food intake, culinary workshops to stimulate vegetables and fruit intakes and about portion size. The program will be evaluated through the application of the same questionnaires used for the diagnosis and a discussion group. The complexity of issues related to food selection requires interdisciplinary actions and comprehensive approaches.
Keywords: Food and nutrition education; athletes; food behavior